Using ACHIS to Analyze Nursing Health Promotion Interventions for Vulnerable Populations in a Community Nursing Center: A Pilot Study - Woi-Hyun S. Hong; Sally Peck Lundeen (Elsevier, 2009)
The purpose of the study was to describe the health promotion interventions of nurses serving a low-income urban population in an academic community nursing center (CNC) in Wisconsin. Methods: The Omaha System (OS) was used to code client problems and nursing interventions for 9,839 visits at the CNC. A dataset created by the Automated Community Health Information System (ACHIS), a computerized clinical information system, was used. A pilot testing was performed with the ACHIS data repository. Each intervention was linked to a nursing diagnosis coded with modifiers as either actual or potential problems or health promotion issues. The Lundeen's Comprehensive Community-based Primary Health Care Model (CCPHCM) which emphasizes primary prevention and health promotion activities served as the conceptual framework for this study. Results: A total of 58,747 modifiers were documented for 58,747 nursing diagnoses where a total of 9,836 nursing interventions were provided to 9,839 community center visits at the CNC. Although a majority of the nursing diagnoses (61.8%) were coded as actual problems as might be expected for this vulnerable population, 38% of the client problems were documented as potential problems (20.6%) and health promotion issues (17.7%.) Health Teaching, Guidance and Counseling (38.9%) and Case Management (25.8%) were the most frequently coded interventions. Conclusion: This research adds to the understanding of the importance of nurses' interventions toward health promotion with the vulnerable population. This preliminary analysis suggests that the ACHIS provide a clinical information system for collecting, storing, processing, retrieving, and managing clinical data in a data repository. [Asian Nursing Research 2009;3(3):130-138]